Dissection of Mechanisms of a Chinese Medicinal Formula: Danhong Injection Therapy for Myocardial Ischemia/Reperfusion Injury In Vivo and In Vitro. (3rd June 2013) - Guan, Yue; Yin, Ying; Zhu, Yan-Rong; Guo, Chao; Wei, Guo; Duan, Jia-Lin; Wang, Yan-Hua; Zhou, Dan; Quan, Wei; Weng, Yan; Xi, Miao-Miao; Wen, Ai-Dong
Abstract : Traditional Chinese medicine uses a systemic treatment approach, targeting multiple etiological factors simultaneously. Danhong injection (DHI), a very popular Chinese medicine injection, is reported to be effective for many cardiovascular conditions. The primary active ingredients of DHI, and their systemic and interrelated mechanism have not been evaluated in an established myocardial ischemia/reperfusion (MI/R) model. We identified the main active constituents in DHI, including hydroxysafflor yellow A (A), salvianolic acid B (B), and danshensu (C), by HPLC fingerprint analysis and assessed their effect on MI/R rats and cardiomyocytes. These 3 compounds and DHI all decreased the levels of IL-1, TNF- α, and MDA, increased those of IL-10 and SOD activity in vivo and in vitro, and had antiapoptotic effects, as shown by flow cytometric analysis and TUNEL assay. Moreover, these compounds increased phosphorylation of Akt and ERK1/2 in cardiomyocytes. Interestingly, we found compound A exerted a more prominent anti-inflammatory effect than B and C, by decreasing NF- κ B levels; compound B had more powerful antioxidative capacity than A and C, by increasing Nrf2 expression; compound C had stronger antiapoptotic ability than A and B, by lowering caspase-3 activity. Our results elucidate the mechanisms by which DHI protects against MI/R induced injury.